2017
DOI: 10.3892/ol.2017.7578
|View full text |Cite
|
Sign up to set email alerts
|

A novel synthetic ursolic acid derivative inhibits growth and induces apoptosis in breast cancer cell lines

Abstract: The present study investigated the anticancer functions of ursolic acid (UA) and its novel derivatives, with a nitrogen-containing heterocyclic scaffold and the privileged fragment at the C-28 position on apoptosis induction, cell proliferation and cell cycle in human BC lines. UA was chemically modified in the present study to increase its antitumor activity and bioavailability. A novel UA derivative, FZU3010, was synthesized using a nitrogen-containing heterocyclic scaffold and a privileged fragment at the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…Li and colleagues [ 88 ] synthesized novel ursolic acid derivative 42 ( Figure 4 , Table 2 ) with a nitrogen-containing heterocyclic scaffold and the privileged fragment at the C-28 position by treating UA with acetic anhydride (Ac 2 O) in dry pyridine under the 4-dimethylaminopyridine (CH 3 ) 2 NC 5 H 4 N) at room temperature for 2 h. The 3-acetylated UA was treated with oxalyl chloride at room temperature for 3 h to produce an intermediary 28-acyl chloride. This compound was then mixed at room temperature for 2 h to synthesize compound 42 .…”
Section: Pyrazolementioning
confidence: 99%
See 2 more Smart Citations
“…Li and colleagues [ 88 ] synthesized novel ursolic acid derivative 42 ( Figure 4 , Table 2 ) with a nitrogen-containing heterocyclic scaffold and the privileged fragment at the C-28 position by treating UA with acetic anhydride (Ac 2 O) in dry pyridine under the 4-dimethylaminopyridine (CH 3 ) 2 NC 5 H 4 N) at room temperature for 2 h. The 3-acetylated UA was treated with oxalyl chloride at room temperature for 3 h to produce an intermediary 28-acyl chloride. This compound was then mixed at room temperature for 2 h to synthesize compound 42 .…”
Section: Pyrazolementioning
confidence: 99%
“…The results indicated that 42 significantly increased the number of SUM149PT and HCC1937 cells lines in the G 0 /G 1 phase in a dose-dependent manner. Compound 42 significantly induced apoptosis in breast cancer more than UA [ 88 ]. Chen et al [ 89 ] also synthesized 42 , which exhibited a remarkable growth of the inhibitory effect against HL-60 cells leukemia cells with an IC 50 value of 0.91 µM, approximately 100-fold more potent than UA [ 89 ].…”
Section: Pyrazolementioning
confidence: 99%
See 1 more Smart Citation
“…To enhance the bioavailability and anticancer activities, UA was chemically modified by Li et al Using a nitrogenous heterocyclic scaffold and a privileged fragment at C-28, they synthesized a new derivative FZU3010. The results of Sulforhodimine B assay and flow cytometry showed that FZU3010 inhibited proliferation and induced apoptosis in SUM149PT and HCC1937 cell lines [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was also observed that UA inhibited inflammation in BC cells by down-regulating NF-κB, thus halting further progression [ 37 ]. A synthetic derivative of UA, FZU3010 caused cell cycle arrest in BC cells at S and G0/G1 phase leading to programmed cell death [ 50 ].…”
Section: Introductionmentioning
confidence: 99%